Attracting accounting and finance graduate talent – beyond the Big Four - Jackson, D.; Richardson, Julia; Michelson, G.; Munir, R. (2021)
This study responds to ongoing challenges with recruiting quality graduate talent in the accounting/finance industry, critical given transforming labour market requirements. Drawing on Person-Organisation Fit (POF) theory, we explore what attracts 475 Accounting/Finance students to graduate roles, their preferences for different organisation types, and influences on career decision-making. Supporting earlier work, we evidence dominating preferences for ‘Big Four’ firms yet discern several appealing features of other organisational types and important intrinsic and extrinsic factors in decision-making. Findings inform stakeholder strategies to support students for sustainable careers in different accounting/finance contexts and improve the recruitment outcomes of all organisation types in the industry.